Interplay of transcription factors in T-cell differentiation and function: the role of Runx - Wong, W.F.; Kohu, K.; Chiba, T.; Sato, T.; Satake, M. (Blackwell Publishing, 2011)
Over the past years, increasing numbers of distinct subsets have been discovered and identified for a T lymphocytes’ entity. Differentiation and function of each T cell subset are controlled by a specific master transcription factor. Importantly, Runt-related transcription factors, particularly Runx1 and Runx3, interplay with these master regulators in various aspects of T cells’ immunity. In this review article, we first explain roles of Th-Pok and Runx3 in differentiation of CD4 versus CD8 single positive cells, and later focus on cross-regulation of Th-Pok and Runx3 and their relationship with other factors such as TCR strength. Next, we provide evidences for the direct interplay of Runx1/3 with T-bet and GATA3 during Th1 versus Th2 commitment to activate or silence transcription of signature cytokine genes, IFNγ and IL4. Lastly, we explain feed-forward relationship between Runx1 and Foxp3 and discuss roles of Runx1 in regulatory T cells’ suppressive activity. This review highlights an essential importance of Runx molecules in controlling various T cell subsets’ differentiation and functions through molecular interplay with the master transcription factors in terms of protein-protein interaction as well as regulation of gene expression.